A Review and Future Prospects of Bounded Rational Behavior in Power Consumers - GAN Lei, ZHANG Peng, ZHU Lin, YANG Tianyu, CHEN Xingying, HUA Haochen, YU Kun (Dianli jianshe, 2025)
[Objective] Amidst the global energy transition， addressing the insufficient regulation capacity of the new electricity system， this study systematically examines the characteristics and applications of bounded rationality behaviors of users. It aims to bridge the theoretical gap in conventional demand-side management caused by oversimplified behavioral assumptions， establish a theoretical foundation for supply-demand interaction optimization， and provide actionable insights for unlocking the potential of demand-side resources.[Methods] An interdisciplinary framework integrating economics and behavioral science theories was developed to analyze bounded rationality in electricity consumption， explicitly distinguishing it from traditional rational behavioral paradigms. User behavior was characterized by four dimensions： the price elasticity of demand， consumer psychology principles， behavioral economics mechanisms， and data-driven behavioral modeling. Furthermore， the implications of bounded rationality were investigated across three key domains： demand response potential assessment， load forecasting accuracy improvement， and user-centric energy decision optimization. The study concluded with a critical evaluation of the current research gaps and proposed methodological advancements for future behavioral characterization studies.[Conclusions] This study contributes to an interdisciplinary framework to enable precision regulation of demand-side resources， fostering innovation in adaptive market mechanisms and dynamic control strategies. Future studies can integrate data-driven analyses of user electricity consumption data to rationally identify critical parameters. This will deepen the fundamental understanding of user energy behaviors， thereby enabling the dual achievement of enhanced system regulation capacity and reduced user energy costs under the “Dual Carbon” goals.